MOTIVASI PEGAWAI DI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN HALMAHERA TIMUR - Kaplale, Muhammad; Lating, Ali; Pora, Rasid (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Human Resource Development is one of the important factors in achieving organisational goals. One of the important instruments in achieving these main goals is motivation. Motivation is one way to build character and coaching, directing each individual. With motivation, the development of each organisational achievement can be seen and measured clearly. In other aspects, motivation can provide a sense of pride for being part of the organisation where they work. Increased motivation provided by leaders is carried out in several aspects, namely in financial management, motivation provided by leaders in improving the performance of public services, given with the aim of improving work performance, emphasis on the importance of rules or provisions that must be implemented properly so that the goals set by the organisation can be realized properly. Motivation in the management of regional revenue is given by leaders because it is a responsibility to the tasks assigned so that it is hoped that the continuity of the organisation, especially in the aspects of budget management discipline and accuracy in completing tasks, can be carried out properly. and Motivation in spending the regional budget aims to support the operational implementation of government administration and development spending which aims to improve people's welfare by opening up jobs to reduce unemployment and alleviate poverty, another dimension of leadership motivation is also an effort to answer the challenges of basic needs both in the education and health sectors by increasing access to fair and equitable services.